Penerapan PSAK 115 Terkait Pengakuan Pendapatan dari Kontrak dengan Pelanggan pada PT Semen Indonesia (Persero) Tbk - Sari, Dina Mufida; Vendy, Vicky (FKIP, Universitas Banten Jaya, 2025)
This study examines how revenue recognition, measurement, presentation, and disclosure are applied at PT Semen Indonesia (Persero) Tbk with the existence of Statement of Financial Accounting Standards (PSAK) 115 which has been in effect since 2020. The research was conducted using a descriptive qualitative method by performing content analysis on the contents of financial statements, related documents, and interviews with several staff from the accounting unit involved in applying PSAK 115. The results of the research at PT Semen Indonesia (Persero) Tbk related to revenue recognition that the process that has been implemented is by PSAK 115. This is evidenced by the application of five stages in recognizing revenue. In the application aspects related to the classification, measurement, presentation, and disclosure of revenue have been applied in accordance with PSAK 115. Furthermore, this study also found that PT Semen Indonesia (Persero) Tbk has made the necessary adjustments to meet the new requirements, including staff training and accounting information system adjustments. These findings indicate that the company has committed to maintaining transparency and accountability in its financial reporting. This research makes an important contribution in understanding the implementation of PSAK 115 in large companies in Indonesia, as well as providing practical guidance for other companies that are or will be implementing this standard.